Carbon dot dressing as a treatment of alkali-induced skin burns - Kuznietsova, Halyna; Ishchuk, Arsen; Bogatyryov, Roman; Bozhenko, Bohdana; Kurylenko, Margaryta; Lysenko, Ivan; Lysenko, Tetiana; Rybalchenko, Taras; Ogloblya, Oleksandr; Ryabchikov, Yury; Zaderko, Oleksandr; Dziubenko, Nataliia (Bìologìčnì studìï, 2024)
Background. Chemical burns, comprising 5–10 % of total burns but causing 30 % of burn-related deaths, are now a notable concern in Ukraine. Current clinical protocols lack specific approaches for chemical burns, and research on this type of burn is limited. Carbon-based nanoparticles show promise for wound healing because of anti-inflammatory, antioxidant, and antibacterial activities. So, the ability of carbon dots obtained from citric acid and urea (further called CD) to improve the healing of alkali-induced skin burn was aimed to be discovered. Materials and Methods. The study was conducted on male Wistar rats. Burn was modeled by application of gauze disc soaked with 3 M NaOH solution on shaved skin of anesthetized rats for 10 min. A CD dressing, consisting of a CD solution (1 mg/mL) mixed with cellulose-based hydrogel that served as a vehicle, was applied to burned skin daily during a 7-day period. There were following groups: control (healthy rats), a burn-only group (rats that received no dressing), a burn + vehicle group (rats that received vehicle dressing), and a burn + CD group (rats that received CD dressing). The study involved monitoring of burn areas, conducting skin histopathology, and performing blood biochemical analyses. Results. The daily CD dressing significantly decreased alkali-induced burn area (by 76 % compared to 40 % in burn-only group) after seven daily dressings. The level of inflammation in the burn site was also less expressed in CD-treated animals, compared to respective controls (non-treated animals and animals treated with Vehicle). There was no substantial systemic toxicity of the burn (of such area) and its healing, manifested by absence of body weight loss, and absence of dramatical changes in serum biochemical parameters (indicators of liver and kidney function). However, animals of all the groups that experienced burns had a significantly lower body weight gain and mesenteric lymph nodes weight compared to healthy rats. Conclusions. So, the application of carbon dots mixed with hydrogel speeded up alkali-induced burn healing without negative impact on the organism.